Seismic modeling of integral abutment bridges in Illinois. (15th June 2018) - Kozak, D.L.; LaFave, J.M.; Fahnestock, L.A.
Highlights: Development of an overall integral abutment bridge nonlinear model. Detailed models for individual components within integral abutment bridges. Pushover behavior of overall bridges and individual bridge components. Bridge and component behavior during 1000-year return period earthquakes. Identification of vulnerable components and potential design modifications. Abstract: Integral abutment bridges (IABs) are a common bridge type used in modern design and construction to prevent damage at the abutment seat from water, dirt, or deicing chemicals penetrating through a compromised expansion joint. Elimination of expansion joints in IABs leads to complex soil-structure-interaction limit states involving the IAB abutment and surrounding soil, as well as unique overall bridge behavior in comparison to non-IABs. Despite this different behavior, there is a lack of studies investigating overall bridge performance of IABs when subjected to seismic loads. Existing seismic IAB studies have typically investigated individual components, such as the interaction between abutment piles and soil or the behavior of superstructure-abutment connections, but the comprehensive behavior of all IAB components when subjected to an earthquake has not been evaluated in an integrated fashion. This study details an IAB model developed for dynamic analysis that simultaneously considers contributions from all critical IAB components. The seismic response of two IABs, one with steel plate girders and another with precast prestressed concrete girders, is evaluated at the design-level shaking using the developed model. The design-level shaking is provided by 20 ground motions, for a 1000-year return period hazard-level, developed for the southern Illinois city of Cairo. Results demonstrate the ability of the IAB model to capture key features of bridge seismic behavior, and they provide a framework for bridge engineers to understand IAB earthquake response and limit states, as well as support recommendations for IAB seismic design in Illinois concerning side retainer anchor bolt size and pier column size.